Tracing the impact of the ECB's asset purchase programme on the yield curve - Fabian Eser; Wolfgang Lemke; Ken Nyholm; Sören Radde; Andreea L. Vladu (European Central Bank (ECB), 2019)
We trace the impact of the ECB's asset purchase programme (APP) on the sovereign yield curve. Exploiting granular information on sectoral asset holdings and ECB asset purchases, we construct a novel measure of the "free-float of duration risk" borne by price-sensitive investors. We include this supply variable in an arbitrage-free term structure model in which central bank purchases reduce the free-float of duration risk and hence compress term premia of yields. We estimate the stock of current and expected future APP holdings to reduce the 10y term premium by 95 bps. This reduction is persistent, with a half-life of five years. The expected length of the reinvestment period after APP net purchases is found to have a significant impact on term premia.
Keywords: C5; E43; E52; E58; G12; 330; Term structure of interest rates; term premia; central bank asset purchases; non-standard monetary policy measures; European Central Bank